The mitochondrial genomes of the zoonotic canine filarial parasites dirofilaria (nochtiella) repens and candidatus dirofilaria (nochtiella) honkongensis provide evidence for presence of cryptic species - Yilmaz, Esra; Dennebaum, Martin Stefan (PLoS neglected tropical diseases, 2016)
Author Summary The mitochondrial genomes of the zoonotic parasite species Dirofilaria repens and Candidatus Dirofilaria hongkongensis were characterized and compared to the genomes of other filariae. The resulting phylogeny is largely in agreement with recent molecular data. C. D. hongkongensis was placed as a sister group to D. repens and both as a common sister to D. immitis. The large genetic difference between D. repens and C. D. hongkongensis further supports the hypothesis that both are distinct valid species. Two canine samples from Thailand that were diagnosed as D. repens are either from a C. D. hongkongensis population that is quite divergent from the Indian population or might represent another currently unrecognized species in the genus.